Women and unions : forging a partnership - Cobble, Dorothy Sue (ILR Press, 1993)
"A crucial new relationship is emerging between women and organized labor. The economic problems facing a majority of working women - low pay, job segregation, the added burden of a "second shift" at home - are now central to the feminist agenda." "At the same time, the labor movement has initiated new ties with women and minority workers, adjusting to fundamental changes in the workplace. Women occupy jobs that are quite different from those held by labor's traditional constituency, the blue-collar hard hat. The new majority tends to work in service jobs, in decentralized workplaces with fewer than fifty employees, and in jobs with less of a permanent, continuous attachment to a single employer." "How can unions and women best serve each other and themselves? In this volume, more than forty scholars and activists integrate their experiences to suggest some answers. They discuss ways to close the wage gap and to meet family needs. They explore both the opportunity and the danger of temporary and part-time work, and try to develop a realistic approach to homework. Finally they document new directions in organizing and representing women, and debate the implications of women moving into union leadership."--BOOK JACKET.